Evaluation of ASTM D 1143/D 1143M-07 and Chinese Code JGJ 106-2014 for Pile Load Testing using Finite Element Method - Aswin Lim; Octavianus Arvin Sukiwan (Civil Engineering Dimension, 2023)
Pile foundation is a structural element utilized to transmit structural load into the soil mass. During design processes, many empirical equations used to estimate axial pile capacity, and a pile load test is conducted to validate the design. In Indonesia, it is common to adopt ASTM D 1143/D 1143M-07 for pile testing. Chinese Code JGJ 106-2014 is another viable option, which has gained popularity recently. This study investigated the load–settlement curves obtained using both codes. The analyses were simulated using the Mohr–Coulomb and the Hardening Soil models. The Hardening Soil model yielded more reasonable load–settlement and load–excess pore water pressure curves than the Mohr–Coulomb model. The reason due to the Mohr–Coulomb model unable to capture the non-linear behavior of soil properly. Furthermore, the results showed that ASTM D 1143/D 1143M-07 and JGJ 106-2014 yielded comparable results. Hence, both methods could be substituted each other.